Structural failure and plasticity : proceedings of the seventh International Symposium on Structural Failure and Plasticity (IMPLAST 2000), 4-6 October 2000, Melbourne, Australia /: proceedings of the seventh International Symposium on Structural Failure and Plasticity (IMPLAST 2000), 4-6 October 2000, Melbourne, Australia. (2000) - Unknown
No abstract available